POLYCYCLIC AROMATIC HYDROCARBONS (PAHs) IN COASTAL SEDIMENTS IN THE NORTH OF VIET NAM - Kha, Pham Thi (Vietnam Journal of Marine Science and Technology, 2014)
Sediment samples were collected at 6 monitoring stations in the coastal area of North Viet Nam from Tra Co to Cua Lo station and were analysed to determinate PAHs contents. The analysic results shown that the content of total 8 PAHs were ranged from 69.56 to 183.88µg/kg dry weight. The content of total 8 PAHs was highest in Cua Lo station in the south, is lowest in Tra Co station in the north. Content of PAHs in dry season were higher than rainy season from 1.1 - 1.9 times. The content of PAHs were under the limitation, but Phenanthrene was exceeded the limitation from 1.02 - 2.66 times at all stations. Three - ring PAHs predominated and, occupied from 40.8 - 90.3 percents of total PAHs. The source of PAHs in coastal sediments in the North of Vietnam was from burning processes.